Dual burden of TB and mental ill-health: Prevalence and associated factors of anxiety and depression among TB patients in Gujarat - Ajay Chauhan; Apurvakumar Pandya; Deepti Bhatt; Vibha Salaliya; Rutu Trivedi; Dixit Kapadia; Prachi Shukla; Amar Shah; Siddharth Chaudhary; Chandrashekhar Joshi; Vivekanand Pandey (Journal of Family Medicine and Primary Care)
Context: The coexistence of tuberculosis (TB) and mental disorder presents a daunting public health challenge. Studies suggest that TB patients often experience co-morbid mental health problems, highlighting a dual burden of illness. However, due to limited research in Gujarat, we cannot draw definitive conclusions or develop targeted mental health interventions for this population. Aim: To investigate the prevalence of depression, anxiety, and associated factors among TB patients from Gandhinagar and Surat cities in Gujarat, India. Settings and Design: The cross-sectional research was conducted in two cities in Gujarat, Gandhinagar and Surat, between October 2021 and July 2023. Methods and Material: Demographic information, anxiety and depressive symptoms, and perceived TB stigma were assessed at baseline (within 1 month of treatment initiation) and at the endpoint (6 months posttreatment) using a self-constructed tool for assessing risk factors and standardized instruments, namely, the Patient Health Questionnaire-4, and the Perceived TB Stigma Scale (12 items). Results: The study population had a mean age of 31.57 ± 12.34 years. The prevalence of anxiety and depression symptoms was found to be 10.5% (749) and 5% (359), respectively, at the baseline. TB patients with high perceived TB stigma and who had been sick for over six months were 3.1 times more likely to experience anxiety symptoms (Adjusted Odds Ratio (AOR) = 3.10, 95% CI: 2.22, 4.23) and 1.6 times more likely to experience symptoms of depression (Adjusted Odds Ratio (AOR) = 1.60, 95% CI: 1.12, 2.53). Gender, occupation, and socioeconomic level were significantly associated with both anxiety and depression (P < 0.05). Being single (AOR: 3.29; 95% CI: 2.45–7.53), low socioeconomic status (AOR: 5.41; 95% CI: 2.44–7.97), and being on TB treatment (AOR: 4.35; 95% CI: 1.83–15.65) were strongly associated anxiety and depressive symptoms. Conclusion: The findings of the current study indicate that TB patients experience a considerable burden of symptoms of both anxiety and depression. It highlights the need for incorporating mental healthcare support within TB care programmes.